MPEG Video Transmission Over Error-Resilient AWGN Wireless Channel - Al-Suhail, Ghaida. A.; Abdallah, Turki Y. (Basrah Journal for Engineering Sciences, 2007)
The goal is how to estimate video quality of MPEG TCP-Friendly video streaming over robust wireless channel against frequent packet loss. In this paper, a Forward-Error-Correction (FEC) scheme is used as an intra-protection control over an Additive White Gaussian Noise (AWGN) wireless channel behind wired links. For this purpose, we propose Variable Frame Rate based on TCP-Friendly Rate Control (VFR-TCP) algorithm to evaluate the predicted frame rate of MPEG-4 video streaming. Quality of Service (QoS) is also evaluated by the predicted quantizer scale Q for the case that the network throughput is assumed to be equal to the required bandwidth. As a result, we obtained a good and reasonable perceived video quality over a noisy wireless channel, by varying the channel error rate or the channel SNR where AWGN and a coded BPSK scheme are dominated.